An Analysis of the Translation Procedures Used by Digital Happiness - Yudha, Galang Tirta (Universitas Islam Negeri Raden Intan Lampung, 2022)
This research wanted to know what kind of and the best Translation Procedures were used by Digital Happiness while translating DreadOut and DreadOut 2. DreadOut and DreadOut 2 are video games that occurred in Bandung and follow the story of Linda combating various Indonesian mythical creatures. This analysis research used documentation in collecting the data. The instruments of this research were documents, field notes, the theory of Translation Procedures by Newmark. There were 3 major steps that were used to analyze the data: First, determined and then isolated Common Component (CC) of the meaning of the lexicon in English and Indonesia; Second, determined and then isolated Diagnostic Component (DC) of the meaning of the lexicon in English and Indonesia; Determined the similarity (+) and difference (-) in the translation in a column. Finally, triangulation was used to validate the data analysis result. After analyzing the DreadOut and DreadOut 2 it was found that Digital Happiness were using certain Translation Procedures to translate their games; Transference, Neutralisation, Cultural Equivalent, Functional Equivalent, Synonymy, Shift, Paraphrase, and Translation Note, Addition, Glasses. With Cultural Equivalent being the best Translation Procedure on the list